Atonement (Universal Pictures, 2007)
Through a series of catastrophic misunderstanding Robbie Turner (James McAvoy) is accused of a crime he did not commit. this accusation destroys Robbie and Cecilia's (Keira Knightley) new found love and dramatically alters the course of their lives.